IMPLEMENTASI PENATALAKSANAAN KASUS GIZI BURUK DI WILAYAH KERJA PUSKESMAS CILACAP UTARA I (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2017)
Severe malnutrition may increase the risk of mortality, morbidity from infectious diseases, and delayed physical likewise cognitive development. The incidence of severe malnutrition in Cilacap in 2013 was 112 cases and increased in 2014 to 116 cases. Therefore, it was necessary to know and analyze the implementation of severe malnutrition management, in terms of input, process, and output components. This study used qualitative research, using case study design on 6 informants selected with eligibility criteria. Data collection was conducted by observation, in-depth interviews, and document studies. Validity test was done with triangulation. Data were analyzed with Miles and Huberman analysis model. It showed that the management of severe malnutrition was good enough. It could be seen from the input components (the number of health volunteers and the infrastructure facilities have been fulfilled, while the number of nutrition officers was still less and their role have not been well implemented), the process components (preparation stage was good, while organizing has not well structured, implementation and severe malnutrition service flow have not well run as procedure), and the output components (malnourished children under five have treated for 3 months and there was an improvement to better nutritional status).